Cost models for improved vehicle assembly line performance. (2017) - Rane, Arun Bhiva; Sunnapwar, Vivek K.; Khot, S.M.
The viability of any manufacturing plant is a function of time and cost. Automobile manufacturing is the most competitive sector. The objective of this paper is to provide a detailed description of the development of the relationships between cost of failure and time lost due to equipment failure, cost of inventory and time lost due to shortages of material, cost of set up and time lost due to set up, cost of absenteeism and time lost due to absenteeism, and cost of material handling and time lost due to material handling. Relationships are established scientifically using regression modelling, simulation and discussions with domain experts. Results are validated in an operational vehicle assembly line. The results demonstrate that the established models follows a cubic relationship as against the hyperbolic relationship previously reported in literature. Further, an improved model strong 17 strong constraints is presented which may be useful for managers in taking cost-based decisions to improve the throughput.